Crédito habitacional no Brasil: governo, mercado e o acesso à moradia - Montagnana, Giovanni Danielli (2016)
This paper aims to present the main investment plans in housing by the federal government, with greater emphasis on Housing Financial System (SFH) to the program My House, My Life. It also establishes a survey of the Real Estate Financial System (SFI) under the aegis of the new legislative and financial practices that mainly cater to middle and upper class. It then presents an analysis of public finances in São Paulo and the resources devoted to housing for low-income population